If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 4)(8x + -4) = y Reorder the terms: (4 + 8x)(8x + -4) = y Reorder the terms: (4 + 8x)(-4 + 8x) = y Multiply (4 + 8x) * (-4 + 8x) (4(-4 + 8x) + 8x * (-4 + 8x)) = y ((-4 * 4 + 8x * 4) + 8x * (-4 + 8x)) = y ((-16 + 32x) + 8x * (-4 + 8x)) = y (-16 + 32x + (-4 * 8x + 8x * 8x)) = y (-16 + 32x + (-32x + 64x2)) = y Combine like terms: 32x + -32x = 0 (-16 + 0 + 64x2) = y (-16 + 64x2) = y Solving -16 + 64x2 = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 64x2 = 16 + y Combine like terms: -16 + 16 = 0 0 + 64x2 = 16 + y 64x2 = 16 + y Divide each side by '64'. x2 = 0.25 + 0.015625y Simplifying x2 = 0.25 + 0.015625y Reorder the terms: -0.25 + x2 + -0.015625y = 0.25 + 0.015625y + -0.25 + -0.015625y Reorder the terms: -0.25 + x2 + -0.015625y = 0.25 + -0.25 + 0.015625y + -0.015625y Combine like terms: 0.25 + -0.25 = 0.00 -0.25 + x2 + -0.015625y = 0.00 + 0.015625y + -0.015625y -0.25 + x2 + -0.015625y = 0.015625y + -0.015625y Combine like terms: 0.015625y + -0.015625y = 0.000000 -0.25 + x2 + -0.015625y = 0.000000 The solution to this equation could not be determined.
| -6x+7(2x+6)=142 | | -90-6x=48-12x | | -100=n+8 | | 7x+5(4-2x)=5 | | (8x+4)(8x-4)=y | | -4(-3x-8)-4x+8= | | (x-35)+90+43=180 | | 6(p+8)= | | -90-6x=48-12x | | -4(-3x-8)-4x+8= | | 6(p+8)= | | x+28500-y=371500 | | 6(p+8)= | | x+28500-y=371500 | | 15/30=6/x | | 7x=3(3x-4) | | 7x=3(3x-4) | | 7x=3(3x-4) | | 175*20+25= | | -4=2/3m+6 | | -6x+7(-2x+6)=142 | | x+28500-x=371500 | | -4[p+1]=-2[8-2p] | | p+26.3=12.74 | | 18-50= | | v/4-2=8 | | x+28500-x=371500 | | -16+3x=x+4x | | p+26.3=12.74 | | x+28500-x=371500 | | -6x+7(-2x+6)=142 | | [(2x-45-20)2]-5=0 |